Os/Si nanocomposites as excellent hydrogen evolution electrocatalysts with thermodynamically more favorable hydrogen adsorption free energy than platinum. (September 2017) - Cheng, Yafei; Fan, Xing; Liao, Fan; Lu, Shunkai; Li, Youyong; Liu, Liangbin; Li, Yanqing; Lin, Haiping; Shao, Mingwang; Lee, Shuit-Tong
Abstract: The development of highly efficient electrocatalysts for hydrogen evolution reaction is a fundamental undertaking of the hydrogen economy. Herein, we investigated the electrocatalytic performance of M/Si (M = Os, Rh, Pt, Pd, Re, Ru, Au or Ag) nanocomposites for hydrogen evolution reaction. The results show that Os/Si nanocomposites exhibit the best catalytic efficiency with a negligible onset overpotential (−25 mV), a small Tafel slope of −24 mV dec −1 and remarkable long-term stability. Of most importance, at a current density of the typical industrial production (−1000 mA cm −2 ), the energy conversion efficiency of the Os/Si nanocomposite is 29.3% higher than that of the commercial 40 wt% Pt/C. The density functional calculations reveal that such outstanding catalytic activity of the Os/Si catalyst arises from the thermodynamically more favorable hydrogen adsorption free energy (Δ G H* = −0.03 eV) at the osmium/silicon interfaces than that on platinum (Δ G H* = −0.09 eV) or osmium (Δ G H* = −0.26 eV). Graphical abstract: Os/SiNW exhibits a thermodynamically favorable hydrogen adsorption free energy of −0.03 eV endowing its excellent electrocatalytic activity and stability for HER, which even surpasses 40 wt% Pt/C at overpotentials above −60 mV. Highlights: Os/Si has a thermodynamically favorable hydrogen adsorption free energy. Os/SiNW composites show a low Tafel slope of −24 mV dec −1 . The performance of Os/SiNW catalysts exceeds Pt/C at high overpotentials.